Exploiting plants for glutathione (GSH) production: uncoupling GSH synthesis from cellular controls results in unprecedented GSH accumulation - Liedschulte, Verena; Rausch, Thomas (Plant biotechnology journal, 2010)
Glutathione (GSH) is a key factor for cellular redox homeostasis and tolerance against abiotic and biotic stress (May et al., 1998; Noctor et al., 1998a). Previous attempts to increase GSH content in plants have met with moderate success (Rennenberg et al., 2007), largely because of tight and multilevel control of its biosynthesis (Rausch et al., 2007). Here, we report the in planta expression of the bifunctional γ-glutamylcysteine ligase—glutathione synthetase enzyme from Streptococcus thermophilus (StGCL-GS), which is shown to be neither redox-regulated nor sensitive to feedback inhibition by GSH. Transgenic tobacco plants expressing StGCL-GS under control of a constitutive promoter reveal an extreme accumulation of GSH in their leaves (up to 12 μmol GSH/gFW, depending on the developmental stage), which is more than 20- to 30-fold above the levels observed in wild-type (wt) plants and which can be even further increased by additional sulphate fertilization. Surprisingly, this dramatically increased GSH production has no impact on plant growth while enhancing plant tolerance to abiotic stress. Furthermore, StGCL-GS-expressing plants are a novel, cost-saving source for GSH production, being competitive with current yeast-based systems (Li et al., 2004).